The slowness of language, the speed of capital : conflicting temporalities of the "green transition" in the Swedish north - Nuottaniemi, Andreas (Multilingua, 2024)
Following substantial investments in battery production and fossil-free steel, a few select places in northern Sweden are currently undergoing rapid economic and cultural changes. The aim of this article is to explore the role language education plays for three different groups of (im)mobile subjects â€“ refugees, labor migrants, and cosmopolitan elites â€“ in the ongoing social transformations. By using the time-consuming and ideologically charged social practice of teaching and learning languages as a lens, it is argued that although framed as a sustainability project, the pace of the transformation is set by the accelerating logic of capitalism, posing a challenge to the democratic planning of inclusive local communities, as well as to societal subsystems characterized by much slower temporal regimes. Hence, although Sweden is committed to a â€œjust transitionâ€ as part of the Paris Agreement, some are obviously benefiting much more than others from this transition. This paper further highlights the potentially high costs for the local communities that â€œwinâ€ the bids for the new green industries. Apart from considerable economic costs in the present, another result might also be increased social stratification and weakening social cohesion in the long term. Ett fÃ¥tal utvalda plats i norra Sverige upplever nu hastiga ekonomiska och kulturella fÃ¶rÃ¤ndringar till fÃ¶ljd av omfattande investeringar i batteriproduktion och fossilfritt stÃ¥l. Syftet med den hÃ¤r artikeln Ã¤r att utforska vilken roll sprÃ¥kundervisning spelar fÃ¶r tre olika grupper av (im)mobila subjekt â€“ flyktingar, arbetsmigranter och kosmopolitiska eliter â€“ i den pÃ¥gÃ¥ende samhÃ¤llsomvandlingen. Genom att utgÃ¥ frÃ¥n de tidskrÃ¤vande och ideologiskt laddade sociala praktikerna undervisning och lÃ¤rande av sprÃ¥k visas hÃ¤r att Ã¤ven om samhÃ¤llsomvandlingen ofta ramas in som ett hÃ¥llbarhetsprojekt sÃ¥ bestÃ¤ms hastigheten av kapitalismens accelererande logik, vilket innebÃ¤r utmaningar fÃ¶r demokratiska planeringsprocesser, likvÃ¤l ...